Upper Clyde Shipbuilders Work-in, 1972 (London, 1972)
1972 1970-74 "Upper Clyde Shipbuilders Work-in, 1972" [BW0025], 1972, Trades Union Congress New Year message 1972 from UCS workers to their supporters. The announcement of the withdrawal of government support for Upper Clyde Shipbuilders (UCS) was made in June 1971. The first redundancies were made on July 30 and the same day Jimmy Reid, the shop stewards' convenor, called for an occupation of the shipyards to prevent their closure. The work-in was supported by mass demonstrations and regional strikes, and only ended in October 1972 when the Government guaranteed work for all four shipyards on Clydeside with most of the original 8000 jobs retained. The UCS work-in stimulated a wave of workers' occupations throughout Britain, estimated at 190 between 1971-1975.